'Accept with revisions': regulating the language of student writing. (2nd November 2018) - Mäntynen, Anne
Abstract: This article focuses on the regulation of student writing by exploring a specific form of such writing, the maturity test . In Finnish universities, the maturity test is a compulsory part of a bachelor's degree in which students demonstrate their familiarity with the topic of their bachelor's thesis, as well as their mother tongue skills. Maturity tests are written, revised and assessed in a multiphase process in which students receive both written and oral feedback on their texts before submitting the final version for acceptance. The focus of this paper is on feedback conversations between the student and the reviser. The questions explored are: (1) what aspects of the texts and their acceptability are brought up in the conversations and by whom, and (2) what kinds of normative systems do the participants orient to? The findings suggest that there are several kinds of these systems, and that the participants orient to polycentric systems of norms, which are tied to a various centring institutions . The data include regulatory documents, maturity tests, and feedback conversations.